Prevalence of HIV, Hepatitis B and C Infections and an Assessment of HCV-Genotypes and Two IL28B SNPs among People Who Inject Drugs in Three Regions of Nepal - Kinkel, Hans-Tilmann (PLoS One, 2015)
As part of a comprehensive health care programme for people who use drugs in Nepal, HIV and viral hepatitis B and C status—including risk factors, HCV-genotypes and co-infections—as well as two IL28B Single-nucleotide polymorphisms (SNPs) were assessed for a random sample of 401 people who inject drugs in three regions of Nepal: mid-western Terrai (Nepalgunj), the eastern region (Dharan, Biratnagar) and the central region (Kathmandu, Lalitpur and Chitwan). Individuals were included who showed at least a minimum of health care seeking behaviour. This latter criterion was defined by being registered with any organisation offering health services. The average age of the participants was 30.5 yrs, and the average length of intravenous drug use was 8.5 yrs. The prevalence rates of HBsAg, anti-HIV antibodies and HCV-RNA were 3.5%, 13.8% and 41.9%, respectively. Spontaneous HCV clearance was evident in 16% of all of those who tested positive for anti-HCV antibodies. Independent risk factors for HCV-RNA positivity were age, gender, geographical region, duration of injecting drug use, history of imprisonment and HIV co-infection. In the age group ≤24 yrs, the rate of spontaneous HCV clearance was 43.5%. Overall, 59.8% of HCV infections were caused by HCV genotype 3 and 40.2% by HCV genotype 1. No other HCV genotypes were identified in this study. The IL28B SNP rs12979860 and rs8099917 were identified in 122 patients, and 75.4% of all participants had both favourable genotypes rs12979860 C/C and rs8099917 T/T.